Mathematics

Make S the subject of the formula: (V = frac{K}{sqrt{T-S}})

Make S the subject of the formula: (V = frac{K}{sqrt{T-S}})
  • A.
    (T-frac{K^2}{V^2} = S)
  • B.
    (T+frac{K^2}{V^2} = S)
  • C.
    (T-frac{K^2}{V} = S)
  • D.
    (T-frac{K}{V} = S)
  • E.
    (T-frac{K}{V^2} = S)
Correct Answer: Option A
Explanation

(V = frac{K}{sqrt{T-S}})
square both sides of the equation
(V^2 = frac{K^2}{T-S})
cross multiply
(V^2 T – S = K^2)
(T – S = frac{K^2}{V^2})
(T = frac{K^2}{V^2} + S)
(T – = frac{K^2}{V^2} = S)